2021
DOI: 10.1101/gad.348174.120
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical reactivation of transcription during mitosis-to-G1 transition by Brn2 and Ascl1 in neural stem cells

Abstract: During mitosis, chromatin condensation is accompanied by a global arrest of transcription. Recent studies suggest transcriptional reactivation upon mitotic exit occurs in temporally coordinated waves, but the underlying regulatory principles have yet to be elucidated. In particular, the contribution of sequence-specific transcription factors (TFs) remains poorly understood. Here we report that Brn2, an important regulator of neural stem cell identity, associates with condensed chromatin throughout cell divisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Thus, we asked whether the phospho-S5-mediated regulation of ID2 stability through controlled interaction with core APC might provide the cross-talk between the intrinsic mitotic regulatory machinery and reactivation of tissue-specific transcriptional programs by bHLH transcription factors. Interestingly, recent work reported that bHLH transcription factors dissociate from mitotic chromosomes 35 . As the ubiquitously expressed E proteins are obligate partners of all bHLH transcription factors and cannot bind DNA in the presence of ID2 27 , we measured E-protein-mediated transcription with an E-box-luciferase reporter in cells transiting through mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we asked whether the phospho-S5-mediated regulation of ID2 stability through controlled interaction with core APC might provide the cross-talk between the intrinsic mitotic regulatory machinery and reactivation of tissue-specific transcriptional programs by bHLH transcription factors. Interestingly, recent work reported that bHLH transcription factors dissociate from mitotic chromosomes 35 . As the ubiquitously expressed E proteins are obligate partners of all bHLH transcription factors and cannot bind DNA in the presence of ID2 27 , we measured E-protein-mediated transcription with an E-box-luciferase reporter in cells transiting through mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…Live-cell imaging of the germinal layers at the lateral ganglionic eminence (LGE) in the ventral telencephalon described a complex lineage, with Radial Glia (RG) NS cells in the Ventricular Zone (VZ) at the top of a hierarchy that includes apically-dividing short neural precursors (SNPs), sub-apically dividing progenitors (SAPs), and intermediate progenitors (IPs) that divide in the Sub Ventricular Zone (SVZ) (Pilz et al, 2013;García and Harwell, 2017). In the LGE, Ascl1 is excluded from (Gsx2 expressing) RG cells (Roychoudhury et al, 2020), starting to be expressed in apically dividing progenitors, most likely SNPs (Soares et al, 2021) (Figure 2A).…”
Section: Multiple Ascl1 Functions Along the Neuronal Lineagementioning
confidence: 99%
“…Live-cell imaging experiments using fluorescently tagged proteins have been a major drive in recent studies characterizing how TFs interact with mitotic chromosomes (box 1). Using this approach, a growing number of TFs has been shown to colocalize with condensed chromosomes during mitosis, a property herein referred to as 'mitotic chromosome binding' (MCB) [8,20,[27][28][29]. Despite the growing number of TFs reported to display MCB, it remains less clear how this binding is mediated.…”
Section: Electrostatic Interactions and Mitotic Chromosome Bindingmentioning
confidence: 99%
“…In spite of decreased global histone acetylation levels during mitosis, it is at this stage that the negative electrostatic field of DNA is strongest, as result of high chromatin compaction and H3ser10 phosphorylation throughout chromosomes [ 4 ]. Thus, electrostatic interactions between proteins and DNA play a more prominent role in the context of condensed chromosomes during mitosis, or in DNA-dense and heterochromatic regions in the interphase nucleus [ 8 , 20 ]. Hence, binding of TFs to mitotic chromosomes should be discussed considering the different types of interactions that TFs may engage on mitotic chromatin.…”
Section: Distinct Forces Mediate Binding Of Tfs To Chromatinmentioning
confidence: 99%
See 1 more Smart Citation